Using Technology to Enhance Pedagogies in Rural Geography Primary Classroom in the Twenty-First Century. Issue 3 (3rd July 2018) - Felix, Alan; Condy, Janet; Chigona, Agnes
ABSTRACT: The purpose of this research was to explore how two rural primary teachers used technology to enhance their pedagogical and content knowledge of Geography in their everyday teaching and learning. Hence the theory of Koehler and Mishra's Technological, Pedagogical and Content Knowledge (TPACK) framed this research. Although the Intermediate Phase curriculum provides a general education experience, teachers need to adopt teaching strategies that deliver Geographical knowledge, skills and values which enable learners to function effectively and responsibly. A qualitative research design was employed for this study using interviews and observations. Two teachers were purposively selected for this study. The findings indicate that the two teachers used technology, to varying extents, to enhance their pedagogy.